Efficiency of internal controls in financial managament: A review from the audit perspective - Anačkov Darko (Ekonomija: teorija i praksa)
The effectiveness of internal controls in financial management is crucial for ensuring the integrity, accuracy, and legality of financial transactions and reports. From an audit perspective, the internal control system is analyzed to determine whether it is designed and operated in a manner that reduces risk and helps achieve business objectives. The development of auditing and internal control has evolved through numerous historical and economic changes, emphasizing the fundamental goal of establishing clear financial oversight. Consequently, this study explores the managerial impacts facilitated by internal control, focusing on the intrinsic role of audit as a component of financial oversight.